Achieving public and global health competencies: A teaching case study of Botswana's cervical cancer screening program. Issue 3 (9th February 2018) - Okatch, Harriet; Sowicz, Timothy Joseph; Teng, Helen; Ramogola‐Masire, Doreen; Buttenheim, Alison M.
Abstract: Objectives: To design and implement a case study on the cervical cancer screening program in Botswana to teach public and global health competencies to undergraduate nursing students. Design and Sample: The case study was developed following a review of the literature on the epidemiology and health policies of cervical cancer in Botswana, and an interview with an obstetrician/gynecologist engaged in both clinical practice and research in Botswana. The case study has been implemented over seven semesters to students enrolled in the Nursing in the Community course at the University of Pennsylvania. Approximately 75‐100 students are enrolled each semester. Measures: Student's perceptions of epidemiologic skills gained and group functioning. Students responded to an open‐ended question about lessons learned and offered suggestions to improve the learning experience. Results: Faculty assessment of student deliverables demonstrated that students achieved the learning objectives and mastered necessary competencies. More than 70% (n = 69) of the students indicated that they acquired relevant skills at greater than a satisfactory level. Generally, students had great experiences working in groups measured across five dimensions: engagement/contribution, creativity/resilience, on task/works independently, social interaction/communication, and preparedness . However, isolated cases of poor group functioning were reported for engagement/contribution, and creativity/resilience . Conclusion: The case study, which has been revised with respect to length, content and group processes, has been valuable in educating undergraduate nursing students in a more engaging way that mimics real life public health nursing scenarios. Students achieved both public and global health competencies through participation in the case study.